Automatic Continuity Test Machine (CT) Using Proximity Sensors, Photoelectric Sensors and Programmable Logic Controllers (PLC) Systems: The case at PT. “V” Batam Indonesia - Jhon Hericson Purba; Irwanto Zarman Putra; Ridwan Ridwan; Hari Salam (JURNAL INTEGRASI, 2023)
Continuity test Machine (CT) is a tool for detecting damage to the current connection on the AC plug cable. The problem with PT “V” is that it still uses a manual system. So that it is updated to an automatic continuity test machine by manual measurement using a "caliper" and another using an automatic continuity test machine (CT). The results obtained (CT) using a proximity sensor, photoelectric as a detector for the length of the pin connector and a Programmable Logic Control (PLC) system as a controller. Testing the accuracy of the tool using 12 plug and connector samples were the same, namely 10 plug and connector samples that were standard (19.05 +_0.2 mm) and 2 samples that were not standard. Tool performance testing is carried out operating for 184 hours or 23 working days. The results of data analysis found a significant increase, namely an average of 25.94% of the total test results used by the manual Continuity test machine (CT). Totally capable of increasing an average of 970 product units per month, with details reducing by -20.03% good products, increasing by 26.74% good products (standard)